THE INFLUENCE OF LITERATURE AND LANGUAGE ON THE PSYCHOLOGICAL AND SPIRITUAL DEVELOPMENT OF THE PERSON - Pulatova Gulnoza Murodilovna (Bright Mind Publishing, 2025)
This article analyzes the role of literature and language in the psychological and spiritual development of a person from a psychological point of view. Language is considered as a key factor in the formation of human consciousness, cognitive processes, emotional stability and the development of social relations. The article analyzes the processes of developing psychological resources, increasing spiritual strength and satisfying spiritual needs through literary experience. Also, the impact of literature and language on personality development from childhood, on such basic psychological processes as self-awareness, communication and social adaptation is highlighted on the basis of scientific theories and practical observations. The article evaluates literature and language as a natural and necessary psychological tool for the healthy psychological development of a person and sustainable spiritual growth.
Keywords: Psychological development, spiritual maturity, emotional intelligence, empathy, personal self-awareness, language and thought, artistic works and spirituality.